International Migration and the Economics of Language - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2014)
This paper provides a review of the research on the economics of language' as applied to international migration. Its primary focuses are on: (1) the effect of the language skills of an individual on the choice of destination among international (and internal) migrants, both in terms of the ease of obtaining proficiency in the destination language and access to linguistic enclaves, (2) the determinants of destination language proficiency among international migrants, based on a model (the three E's) of Exposure to the destination language in the origin and destination, Efficiency in the acquisition of destination language skills, and Economic incentives for acquiring this proficiency, (3) the consequences for immigrants of acquiring destination language proficiency, with an emphasis on labor market outcomes, and in particular earnings. Factors that are considered include age, education, gender, family structure, costs of migration, linguistic distance, duration in the destination, return migration, and ethnic enclaves, among others. Analyses are reported for the immigrant experiences in the US, Canada, Australia, the UK, Germany, Israel and Spain.
Keywords: J15; J24; J31; J61; 330; immigrants; language; bilingualism; human capital; earnings